2011
DOI: 10.1183/09031936.00168010
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine enhances quality of forced spirometry in primary care

Abstract: Forced spirometry is pivotal for diagnosis and management of respiratory diseases, but its use in primary care is suboptimal. The aim of the present study was to assess a web-based application aiming at fostering high-quality spirometry in primary care.This was a randomised controlled trial with 12 intervention primary care units (PCi) and six control units (PCc) studied over 12 months. All 34 naïve nurses (PCi and PCc) received identical training. The PCi units had access to educational material and remote ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
53
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 25 publications
6
53
0
Order By: Relevance
“…However, for large scale studies, one question will be how to achieve high quality in the most efficient way. While other investigators 4,5,[11][12][13]18 have shown good results using feedback on completed tests, the present study shows that if used with relevant instructions, automated real-time feedback of quality grade can also have a significant impact on quality, altering what happens during the session-which of course is very efficient.…”
Section: Discussionmentioning
confidence: 50%
“…However, for large scale studies, one question will be how to achieve high quality in the most efficient way. While other investigators 4,5,[11][12][13]18 have shown good results using feedback on completed tests, the present study shows that if used with relevant instructions, automated real-time feedback of quality grade can also have a significant impact on quality, altering what happens during the session-which of course is very efficient.…”
Section: Discussionmentioning
confidence: 50%
“…We have no evidence of studies with difficult to control asthmatic patients as the next therapeutic step is to introduce monitoring through an e-health system [29][30][31][32][33]. Short term outcomes in our study show a decrease of patients attending emergency room for asthma exacerbations, as well as improved adherence and treatment compliance which is leading to favourable clinical consequences trough improving respiratory function.…”
Section: Conclusion and Discussionmentioning
confidence: 70%
“…An increasingly large number of applications in various medical specialties and in different fields of health are finding these technologies useful [31][32][33][34][35][36].…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…all primary care centres) is expensive and logistically complex. As we understand it, the best option for large primary care centres, with many patients needing spirometric studies, may be to perform the spirometries in a place with proper and periodic training, perhaps by telematic learning [8,13,36,38]. However, in smaller primary care centres with fewer patients and resources to professionally train workers to carry out spirometry, the online alternative may be preferable.…”
Section: Discussionmentioning
confidence: 99%